Statistika v klinické a experimentální medicíně - Rosina, Jozef; Horák, Jiří; Hendrichová, Miluše; Krátká, Karolína; Vrána, Antonín; Živčák, Jozef (Casopis lekaru ceskych, 2012)
The paper presents a brief overview of statistical methods used in clinical and experimental medicine, ranging from basic indicators and parameters of descriptive statistics and hypotheses testing (parametric as well as non-parametric methods) to a description of the most frequently used multivariate methods in medical scientific publications, to logistic regression. The paper also describes Principle Component Analysis (PCA), which is one of the methods used to decrease a data dimensionality. The proper use of statistical methods is demonstrated on specific clinical cases.
Keywords: analýza hlavních komponent; Statistics, Nonparametric; Statistics as Topic; analýza rozptylu; Regression Analysis; logistické modely; neparametrická statistika; Analysis of Variance; multivariační analýza; Data Interpretation, Statistical; statistika jako téma; Principal Component Analysis; Logistic Models; regresní analýza; interpretace statistických dat; Multivariate Analysis